Examination Of the Scientific and Methodological Foundations of The Formation of Network Communication Culture and Digital Etiquette of Faculty Members at The University - Baiteshovna, Seiitkazy Perizat; Toktarovna, Suleimenova Zhansaya; Madina, Tussupbekova; Nurgul, Yrymbayeva; Kamshat, Ushakbayeva; Turalbayeva, Almash (Journal of Posthumanism, 2024)
This research aims to examine the scientific and methodological foundations of the formation of network communication culture and digital etiquette of university faculty members. 245 faculty members with different titles were included in our research. After obtaining information such as age, gender, years of employment, marital status, title and device usage time (DUT) of the participants, the Academic Digitalisation Scale (ADD) and the Academicians' Access to Information and Communication Technologies Scale (AAICTS) were applied. It was determined that individuals with the title of Prof. were more active in using technological tools and equipment (p>0.05) and the extrinsic motivation level, one of the sub-dimensions of AAICTS, was higher in individuals with the title of Prof. (p=0.012). A significant difference was also found between the participants in terms of skills (p=0.047). There is a negative relationship between age and ADD (p=0.009). There was a positive correlation between marital status and AAICTS (p=.033), extrinsic motivation (p=0.003), skill (p=0.021) and training utilisation (p=0.025).A positive correlation was found between the participants' ADD scores and AAICTS and its sub-dimensions (p<0.001). Accordingly, it is thought that incentives related to digitalisation should be provided to all academicians from the beginning of their academic career.